Correspondence Analysis of Indonesian Retail Banking Personal Loans Top Up - Agustino, Andrie; Sumarwan, Ujang; Sartono, Bagus (Indonesian Journal of Business and Entrepreneurship, 2018)
Customer experience can be developed through good database management, and this is an important thing to do in the era of tough retail banking competition especially in the personal loan market competition. Through good database management, banks can understand the transaction pattern and customer behavior in each bank service’s contact point. This research aimed at identifying the personal loans correspondence between socioeconomic variables and top up transaction by using the secondary data from one of Indonesian retail banking. The research method used the correspondence analysis and regression. The result of the research showed that the socioeconomic factors that influenced the debtors to top up personal loans at the confidence level of 5% (0.05) included Age, Marital Status, Dependent Number, Living Status, Education, Region, Job Type, Work Length, Salary, Debt Burdened Ratio (DBR), Credit Tenure, and Credit Limit, and only Gender had no effect on personal loan top up. The socioeconomic factors that were close correspondence with the personal loan top up transactions included bachelor degree, State-Owned Enterprises and goverment civil servant employee, income starting from Rp 5 million, credit period starting from 4 years, dan credit limit starting from Rp 50 million. The findings in this study are expected to be useful for marketers of the banks in developing personal loan products and also in preparing a more targeted marketing strategy so that it becomes more effective and efficient for the banks. In addition, the expected implication is that the customer experience will be better because the product developed will be more customer centric. Keywords: bank, correspondence analysis, personal loans, regression, top up